Characterisation of the antiproliferative constituents and activity of Ficus exasperata (Vahl) on ovarian cancer cells –a preliminary investigation. Issue 18 (17th September 2017) - Bafor, Enitome E.; McKenna, Jennifer; Rowan, Edward G.; Edrada-Ebel, RuAngelie
Abstract: Ovarian cancer is one of the most common gynaecological cancers today. This study therefore investigates the anticancer effects of Ficus exasperata extracts and fractions on ovarian cancer cells. The antiproliferative activity of the crude extracts (1 mg/mL) was assessed using the MTT assay on A2780 (ovarian cancer) cell line. Bio-activity guided fractionation was performed and preliminary identification was further achieved using high resolution mass spectrometry and nuclear magnetic resonance spectroscopy. All crude extracts tested exhibited antiproliferative activity except for the methanol extract which interestingly showed proliferative effects. Five fatty acids were identified from the active fractions (FB1-10 andFB1-12 ).FB1-12 exhibited an IC50 value of 15.20 μg/mL. The least potent fraction (FB1-4 + 5) had an IC50 value of 34.51 μg/mL.H1-HEX andH1-MET exhibited 97.2 and 97.9%, respectively, compared to control. This study therefore provides proof-of-principle that fatty acids of Ficus exasperata exhibit significant antiproliferative effects on ovarian cancer cells. Abstract :